Undeniable Function of Performance Factors on Organizational Accomplishment - Nour Mohammad Yaghoubi (International Review of Management and Marketing, 2017)
Nowadays, performance influences on organizational and social activities that causes to change the nature of performance qualities. Organizational acts comprise the actual outputs or results of an organization as measured against its intended outputs (or goals and objectives). To do this, the researcher has used the organizational performance and performance management theories, application survey and questionnaire. In present research the sample size consists of 270 employees that were selected at random from about 800 employees from near 5 branches of Security of Tabriz at East Azerbaijan in IRAN in 2013. Data analyses were carried out by using factor analysis, structural equation, and Freidman mean ranking test. The results of present study were illustrated that there is significant relationship between factors together, and also considering to the ranking analyses can be said that the information and communication technology of performance factors is the most important factors than others for improving performance in public sector in studied organizations. Also, according to findings of factor analysis all factors have more influence on performance for developing and improving organizational performance.